A GENRE ANALYSIS OF PROMOTIONAL TEXTS IN AN INDONESIAN BATIK INDUSTRY - Kristina, Diah; Hashima, Noor; Hariharan, Hariharan (Indonesian Journal of Applied Linguistics, 2017)
This study explored sales promotion letters (SPLs) and company profiles (CPs) of two prominent batik companies in Solo, Central Java, Indonesia. This essay draws its data from the most important primary source of information on sales promotion letters and company profiles namely words, phrases, and clauses taken from the SPLs and CPs of batik written in Indonesian. Secondary sources were also consulted in this research, among these transcribed data obtained from in-depth interviews with the text writers and buyers. Three SPLs and two batik CPs were analyzed. In addition, two informants (marketing and promotion managers) typifying the text production perspective and two buyers typifying the text consumption perspective were interviewed. This research was guided by theories of genre analysis which focuses on patterns of rhetorical organization and genre-specific language features. This study employed the multi-dimensional and multi perspective model of analysis focusing on textual, socio-cognitive and ethnographic aspects of the texts. This study concludes that the strong Javanese cultural influence has made the underlying intention of gaining profits to be less explicitly stated. Secondly, the textual analysis and the in-depth interviews supported the view that CPs of batik had been ideally used to create a favorable image of the company. Thirdly, the most distinctive feature that differentiated establishing credentials in the Indonesian batik business context had been the utilization of a sense of moral obligation to preserve native culture. Fourthly, the chemistry between writers and readers of SPLs and CPs built a strong foundation for mutual understanding and thus paved the way for making purchases. To conclude, this study has shown how the wider culture and the culture of the discourse community has contributed to the framing and formatting of SPLs and CPs of batik in terms of lexico-grammar, cognitive structuring, intertextuality and interdiscursivity.